2018
DOI: 10.1161/circep.118.006569
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Scar-Related Ventricular Tachycardia Circuits Using Ultra-High-Density Mapping

Abstract: Background Ventricular tachycardia with structural heart disease is dependent on re-entry within scar regions. We set out to assess the VT circuit in greater detail than has hitherto been possible, using ultra highdensity mapping. Methods All ultra high-density mapping guided ventricular tachycardia ablation cases from six high-volume European centres were assessed. Maps were analysed offline to generate activation maps of tachycardia circuits. Topography, conduction velocity and voltage of the VT circuit were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 35 publications
8
73
1
Order By: Relevance
“…Critical isthmus sites were defined a the part of the VT circuit which is delimited by conduction barriers showing the smallest activation region . Length of the isthmus was defined as the distance from the inward wavefront curvature to the outward wavefront curvature . Local signal characteristics were used as an additional parameter.…”
Section: Methodsmentioning
confidence: 99%
“…Critical isthmus sites were defined a the part of the VT circuit which is delimited by conduction barriers showing the smallest activation region . Length of the isthmus was defined as the distance from the inward wavefront curvature to the outward wavefront curvature . Local signal characteristics were used as an additional parameter.…”
Section: Methodsmentioning
confidence: 99%
“…In the dense core of the scar, areas of fibrosis are interrupted by viable fibers that serve as slow conduction pathways. In addition, the tissue surrounding the core of the scar is a 'grey zone' of hypoperfused myocardium with arrhythmogenic properties [73][74][75]. The heterogeneity of the scar as well as the size of the border zone assessed by CMR parameters are all predictors of malignant arrhythmias and appropriate ICD firings in ICM [76][77][78].…”
Section: Ischemic Cardiomyopathymentioning
confidence: 99%
“…[17] Data from human VT studies confirms this general principle. [18] A multicentre study of high-density VT maps found that isthmuses were defined by lines of block, but that multiple entrances and exits were common. Further, in humans, dead ends of activation were also common and regions of activation within dense scar, consistent with inner-loop activation, were also observed.…”
Section: Isthmus Architecturementioning
confidence: 99%
“…Further, in humans, dead ends of activation were also common and regions of activation within dense scar, consistent with inner-loop activation, were also observed. [18]…”
Section: Isthmus Architecturementioning
confidence: 99%
See 1 more Smart Citation